A Typology of Digital Games Focusing on Potential Contributions to Communicating United Nations Sustainable Development Goals - Takuji Takemoto; Kosuke Asakura; Srivichai Nuwaree; Mayuko Mizuno; Tomoki Minami; Mahiro Muramatsu; Sota Yamamoto; Sachiyo Kamimura; Hiroko Oe (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to develop a discussion framework regarding the applicability of online games in higher education institutions for enhancing the understanding of the United Nations Sustainable Development Goals. A typology of online games is discussed, and games are categorised into three types: knowledge education, survival simulation experience and urban design simulation. A quantitative method was applied in this study, with data being collected from game participants who played games of the three types. Ten game attributes were used as potential independent variables to estimate the dependent variable of the participants’ understanding of the SDGs, using structural equation modelling. The developed and verified models indicate that each type of game had a unique impact on the participants’ perceptions of the SDGs based on various factors. This information could be useful as a guide for pedagogists aiming to enhance students’ awareness and understanding of the content and contexts of specific SDGs.